Cell adhesion and migration in the organization of spinal motor neurons - Price, Stephen R. (Landes Bioscience, 2012)
Spinal motor neurons are critical to the ability of animals to move and thus essential to survival. Motor neurons that project axons to distinct limb-muscle targets are topographically organized such that central nervous system position reflects the location of the muscle in the limb. The central positioning of limb-projecting motor neurons arises during development through motor neuron migration followed by a period of coalescence into discrete groupings of motor neurons which project axons to an individual muscle. These so-called motor pools are a common feature of motor organization in higher vertebrates. Recent work has highlighted the critical role for armadillo family member catenin-dependent functions of the cadherin family of cell adhesion molecules in directing the organization of motor neurons. Cadherin function appears to be important for both the motor neuron migration and coalescence phases of the emergence of motor neuron topography. Here, I review this recent work in the context of our understanding of the general development of spinal motor neurons.